2021
DOI: 10.1177/03635465211028980
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Shoulder Stiffness After Arthroscopic Rotator Cuff Repair

Abstract: Background: Postoperative shoulder stiffness (POSS) is a prevalent adverse event after arthroscopic rotator cuff repair (ARCR) that is associated with major limitations in everyday activities and prolonged rehabilitation. Purpose/Hypothesis: The purpose was to develop a predictive model for determining the risk of POSS within 6 months after primary ARCR. We hypothesized that sufficient discrimination ability of such a model could be achieved using a local institutional database. Study Design: Case-control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 57 publications
3
29
1
Order By: Relevance
“…The incidence of postoperative stiffness in patients undergoing ARCR surgery in our study was 49.8% (273/548 patients), which was higher than the 39% reported in the literature [ 1 - 3 , 15 ]. A possible explanation for the higher incidence of post-ARCR shoulder stiffness in the current study could be the higher percentage of female patients, lower mean patient age (<56 years) with lesser opportunity to experience tendon degeneration, and lack of acromioplasty in most patients undergoing ARCR, all of which have been reported as risk factors for post-ARCR stiffness [ 15 ].…”
Section: Discussioncontrasting
confidence: 74%
“…The incidence of postoperative stiffness in patients undergoing ARCR surgery in our study was 49.8% (273/548 patients), which was higher than the 39% reported in the literature [ 1 - 3 , 15 ]. A possible explanation for the higher incidence of post-ARCR shoulder stiffness in the current study could be the higher percentage of female patients, lower mean patient age (<56 years) with lesser opportunity to experience tendon degeneration, and lack of acromioplasty in most patients undergoing ARCR, all of which have been reported as risk factors for post-ARCR stiffness [ 15 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Similarly, Peters et al measured an inferior ROM in abduction and external rotation and documented greater difficulty with reaching behind the back and with overhead activities six months after TCR of partial-thickness tears as compared to repair of full-thickness ones, however without obtaining a statistical significance in their results [14]. A recent clinical registry study by Audigé et al also documented a similar rate of post-operative SS and identified partial tears treatment as a risk factor for developing post-operative SS [25].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous other risk factors have been described in relation to the occurrence of SS, including pre-, intra-and postoperative factors. In the last years, particular interest has been dedicated to the pre-operative risk factors, adding to the well-known ones such as diabetes mellitus and thyroid disease newer ones, like disorders of lipid metabolism and overweight, vitamin D deficiency, gastroesophageal diseases, genetic polymorphisms (e.g., IL-6 and MMP-3) and increased inflammatory changes in the shoulder joint [2,9,24,25,37,[45][46][47][48]. Considered the growing number of possible pre-operative risk factors for SS and the need of specific investigations to assess the presence of many of them, the authors decided to document and include in this study on the role of surgery-related risk factors only age, gender and body mass index, considering the first two also in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results did not demonstrate a strong association between gender and post-operative ASES scores, another area of conflicting findings in the literature. Several studies show female sex to be associated with worse post-operative quality of life, mental health, pain, and functional assessments [ 26 , 27 , 48 , 49 , 50 , 51 ]. Conversely, other studies demonstrate that gender does not influence post-operative outcomes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%